Indikator Keberhasilan Pembangunan Dalam Perspektif Islam - Dedi Junaedi (Institut Agama Islam Sahid (INAIS) Bogor, 2019)
The main objective of a country's economic development is to improve people's welfare. Various indicators of development success have been offered starting from Gross Domestic Product (GDP) and per capita income, the human development index (IPM), the people's welfare index (pledge) and the economic welfare index (Eurostat). However, all of this has not yet reached the perfection of beneficial Islamic economic development, because in an Islamic perspective, these various indicators still have weaknesses, only present worldly statistics, and have not touched the ukhrawi (afterlife) aspect. On that basis, Islam introduces the concept of maqasid al-shariah or benefit as an indicator of development success. The benefit to be achieved includes safeguarding the five main elements of human life, namely faith (tawhid), soul, mind, lineage, and property (wealth).